Magic search getting the best results from your catalog and beyond - Kornegay, Rebecca S.; Buchanan, Heidi E.; Morgan, Hildegard B.; IG Publishing (Chicago, Illinois American Library Association, 2009)
Shows how to increase the power of Library of Congress Subject Heading (LCSH) subdivisions to produce astonishing results from your searches. This title explains how, when used wisely, LCSH subdivisions can save time and provide a level of precision in information retrieval for patrons of the library.
Finding basic treatments and background reading -- Finding how-to guides -- Finding images -- Words, words,-- and numbers -- Finding out about people : individuals and groups -- Finding out about places -- Finding creative treatments : stories, poems, songs, etc. -- Finding true stories : memoirs, observations, and confessions -- Finding primary sources -- It's about time : time periods and chronological subdivisions -- Tools for scholars and other professionals -- Subdivisions that give perspective, put you in control, and amaze others! -- Useful for the humanities -- Useful for the social sciences -- Useful for historical research -- Useful for business topics -- Useful for education topics -- Useful for natural and physical sciences -- Useful for medicine and health topics -- Useful for technology topics -- The baby and the bathwater : recommendations.
Electronic reproduction.
Keywords: Subject heading subdivisions -- Handbooks, manuals, etc; Subject headings, Library of Congress -- Handbooks, manuals, etc; Online library catalogs -- Subject access -- Handbooks, manuals, etc